P‐67: Foldable Ultra‐High‐Resolution AMOLED Panel with Cascade Display‐Driver Integrated Circuit. Issue 1 (28th June 2021) - Lee, Chen-Hui; Huang, Yan-Zhang; Wang, Chien-Kuo; Chang, Ruo-Lan; Kuo, Wen-Yu; Chen, Wei-Chung; Chen, Kuang-Jung; Chang, Chih-Chia
Abstract : Smart portable device equipped with active matrix organic light emitting diode (AMOLED) display is a trend in modern consumer market. In this paper, we present not only a 15.6‐inch foldable 4K ultra high definition (UHD) resolution of low temperature poly‐silicon thin film transistor (LTPS‐TFT) AMOLED panel, but also a display driver integrated circuit (DDIC) module which integrate the cascade structure and high‐magnification demura 6 times compression technology.